Growth performance and biochemical profile of Azolla pinnata and Azolla caroliniana grown under greenhouse conditions - Kösesakal, Taylan; Yıldız, Mustafa (Archives of Biological Sciences, 2019)
Paper description: Azolla is a floating fern that is usually found in paddy water, streams, and pools, in symbiosis with the nitrogen-fixing cyanobacterium Anabaena azollae in the dorsal lobe cavity of the leaves. We determined that in greenhouse A. pinnata grows faster than A. caroliniana and its photosynthetic efficiency is more effective. In addition, palmitic acid, oleic acid and lignoceric acid were found to be predominant in A. pinnata and A. caroliniana. A. pinnata and A. caroliniana contain significant levels of essential amino acids and essential fatty acids and these characteristics make them economically important for human nutrition and the aquaculture sector. Abstract: This study aimed to evaluate the growth performance, pigment content changes, essential amino acids (EAAs), fatty acids (FAs), and proximate composition of Azolla pinnata and Azolla caroliniana grown in a greenhouse. Plants were grown in nitrogen-free Hoagland’s solution at 28±2°C/21±2°C, day/night temperature and 60-70% humidity and examined on the 3rd, 5th, 10th and 15th days. The mean percentage of plant growth and relative growth rate for A. pinnata were 119% and 0.148 gg-1day-1, respectively, while for A. caroliniana these values were 94% and 0.120 gg-1day-1, respectively. Compared to day 3, the amount of total chlorophyll obtained on day 15 decreased significantly (p<0.05) for A. pinnata while the total phenolic and flavonoid contents increased significantly (p<0.05) from the 3rd to the 15th day. However, the total phenolic and flavonoid contents did not differ (p>0.0.5) in A. caroliniana. The crude protein, lipid, cellulose, ash values and the amounts of EAAs were higher in A. pinnata than A. caroliniana. Palmitic acid, oleic acid, and lignoceric acid were found to be predominant in A. pinnata and A. caroliniana. From the plant growth and pigment contents, we concluded that A. pinnata grew faster than A. caroliniana and its photosynthetic efficiency was more effective. https://doi.org/10.2298/ABS190131030K Received: January 31, 2019; Revised: March 22, 2019; Accepted: April 25, 2019; Published online: May 10, 2019 How to cite this article: Kösesakal T, Yıldız M. Growth performance and biochemical profile of Azolla pinnata and Azolla caroliniana grown under greenhouse conditions. Arch Biol Sci. 2019;71(3):475-82.